Influtnce analysis of 09Г2С and 30MnB5 steels thermo cyclic treatment on strength characteristics of road construction machines working bodies - A. P. Scherbakov; A. E. Pushkarev; T. V. Vinogradova (Вестник СибАДИ, 2021)
Introduction. The ways of increasing the reliability of road construction machinery operation are considered. As a result, an option is proposed to replace the used 09Г2С steel with 30MnB5 boron steel. Using the example of a motor grader blade, the force effects on this working body of the road construction machinery are analyzed. In order to increase the level of physical and mechanical characteristics of 09Г2С and 30MnB5 steels, they are additionally exposed to thermo cyclic treatment. The experimental studies about the influence of this type thermal action on the structure and properties of steels are described. The comparative analysis of the obtained characteristics allows making a conclusion about the possibility of the considered replacement.Materials and methods. Through the metallographic analysis the influence of the number of thermal effects cycles on the grain size of steel is investigated. Alongside a set of physical and mechanical characteristics of these steels was determined at various stages of the thermo cyclic treatment.Results. It was determined that an increasing the level of physical and mechanical characteristics of the studied steels is possible through the use of thermo cyclic treatment. This is achieved by producing a fine-grained metal structure with a higher strength. The dependence of the tensile strength and yield strength of the steels under investigation on the number of cycles of thermal action is considered. Some correlation relationships were selected to describe these dependencies. The relationship between the yield stress and ultimate strength of 09Г2С and 30MnB5 steels and the grain size is considered. All investigated dependencies are presented in graphical form.Discussion and conclusion. Based on a comparative analysis of the complex of physical and mechanical characteristics, the conclusion about the possibility of replacing 09Г2С steel with 30MnB5 steel was made.